2019
DOI: 10.1002/hlca.201900032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DFT Methods and Implicit Solvation Models for Anion‐Binding Host‐Guest Systems

Abstract: Although supramolecular chemistry is traditionally an experimental discipline, computations have emerged as important tools for the understanding of supramolecules. We have explored how well commonly used density functional theory quantum mechanics and polarizable continuum solvation models can calculate binding affinities of host‐guest systems. We report the calculation of binding affinities for eight host–guest complexes and compare our results to experimentally measured binding free energies that span the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…This notable difference underlines the importance of regarding explicit counterion effects in calculations. Larger uncertainties are frequently encountered for charged molecular systems in solution [ 54 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This notable difference underlines the importance of regarding explicit counterion effects in calculations. Larger uncertainties are frequently encountered for charged molecular systems in solution [ 54 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results for the pseudorotaxane and (hypothetical) rotaxane formation without counterions and with Cl were compared to calculations, where was obtained in vacuo, and we additionally computed instead, using the COSMO-RS approach [ 58 ] with its fine parametrisation utilising the Cosmotherm programme [ 73 ]. Resulting Gibbs free association energies when no counterions were present are quite off, which is not surprising, as COSMO-RS may yield unreasonable results if charged species are evaluated [ 54 , 59 , 60 ]. On the other hand, results for the Cl complexes agreed very well, with deviations below 3 kJ/mol.…”
Section: Methodsmentioning
confidence: 99%
“…Associated to delocalization problem, self-interaction error associated with DFT is discussed in a recent work of Lee et al [ 71 ]. They discussed about the difference in properties predicted by DFT and HF method for anions.…”
Section: Resultsmentioning
confidence: 99%
“…They discussed about the difference in properties predicted by DFT and HF method for anions. They even suggested that HF theory can be a naive solution to address the problem, shown by DFT methods in predicting the frontier molecular orbital energies and other related properties of anionic systems [ 71 ]. As the systems considered here are zwitterionic natures (with the donor part anionic in nature), hence underperformance of DFT compared to HF may also be addressed as explained by Lee et al [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this context, several groups have developed large datasets of benchmark ionic interaction energies and used these datasets to evaluate the performance of contemporary wavefunction, DFT, and semiempirical methods. , The Houk group has also evaluated DFT methods in conjunction with implicit solvation models to predict the anion binding free energies of eight host–guest complexes in aqueous and organic solvents. The mean absolute deviation in computed binding free energy is 10.5 kJ mol –1 when the B3LYP-D3 functional is used with the conductor-like polarizable continuum model or polarizable continuum model implicit solvent model . However, to evaluate a binding constant to within an order of magnitude of experiment, the error in the computed binding free energy must be smaller than 5.7 kJ mol –1 at 298 K. In quantum chemistry, this error margin is usually referred to as “chemical accuracy”.…”
Section: Introductionmentioning
confidence: 99%